2009
DOI: 10.1080/08860220902779764
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Efficiency of Short-Term Single-Needle Hemodialysis

Abstract: It is widely believed that single-needle (SN) hemodialysis is inferior to conventional double-needle (DN) hemodialysis. The purpose of this study was to compare two SN dialysis regimens using different blood flow rates with conventional DN hemodialysis. The primary outcome measure was ionic dialysance. We studied eight patients (two women, six men) undergoing chronic intermittent DN bicarbonate hemodialysis three times per week on a Cimino-Brescia fistula for at least three months. The study had a prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Hemodialysis patients were treated using the SN technique for the following reasons: to decrease the risk of early arteriovenous fistula failure, to facilitate cannulation for nurses, and to reduce the pain burden for the patient [13][14][15]. However, the use of SN dialysis is mainly limited by the inadequacy of treatment due to lower blood flow, higher recirculation, and shorter treatment time with suboptimal amount of cleared blood volume and low KT/V [11,16]. Recently, several studies have demonstrated comparable effects of SN hemodialysis and DN hemodialysis in patients with chronic kidney disease without any adverse effects [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Hemodialysis patients were treated using the SN technique for the following reasons: to decrease the risk of early arteriovenous fistula failure, to facilitate cannulation for nurses, and to reduce the pain burden for the patient [13][14][15]. However, the use of SN dialysis is mainly limited by the inadequacy of treatment due to lower blood flow, higher recirculation, and shorter treatment time with suboptimal amount of cleared blood volume and low KT/V [11,16]. Recently, several studies have demonstrated comparable effects of SN hemodialysis and DN hemodialysis in patients with chronic kidney disease without any adverse effects [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…In 1979, 8% in Europe and 60% of the hemodialysis patients in Belgium were treated with the single‐needle technique for several reasons: to decrease the risk of an early AVF failure , to facilitate cannulation for nurses, and to reduce the burden of pain for the patient. However, the single‐needle dialysis approach was mainly limited by inadequacy of the treatment due to lower blood flow, higher recirculation and shortened treatment time (caused by the biphasic circulation) with a suboptimal amount of cleared blood volume and low Kt / V , respectively. Moving from double to single‐needle dialysis, the increase of treatment time by about 30 min as demonstrated by Trakarnvanich et al is the only valid option to maintain the adequacy.…”
Section: Summary Of the Single‐needle Phases Of A Cycle In The Equipmmentioning
confidence: 99%
“…Few data are available on short-term SN dialysis and especialy on the dialysis dose measured using a reliable method. Four publications have clearly shown that the technique of hemodialysis in unipuncture delivered an insufficient dose of dialysis [15][16][17][18], which fell below the recommendations of the EDTA and KDOQI [19][20]. These four publications quantified the dose of dialysis by the single-pool Kt/V [15][16][17][18] and the most recent also studied the ionic dialysance and the Kt/V provided by the dialysis monitor [18].…”
Section: Underdialysismentioning
confidence: 99%
“…Four publications have clearly shown that the technique of hemodialysis in unipuncture delivered an insufficient dose of dialysis [15][16][17][18], which fell below the recommendations of the EDTA and KDOQI [19][20]. These four publications quantified the dose of dialysis by the single-pool Kt/V [15][16][17][18] and the most recent also studied the ionic dialysance and the Kt/V provided by the dialysis monitor [18]. Wright and coworkers in the year 2000, were the first to draw attention to the importance of the method of blood sampling in relation to the circuit of unipuncture for the determination of post-dialysis urea in the singlepool method and the risk of a "dramatically optimistic" overestimation of the single-pool Kt/V (due to the contamination of the arterial blood by the recently dialysed venous blood) : among their five patients in SN dialysis, the mean Kt/V taken without precautions measured 1.7 instead of a real value of 1 [15,21].…”
Section: Underdialysismentioning
confidence: 99%